Higher Education Dropouts. Reflections about Managing Retention or Persistence - Pereira Santana, Adrián Esteban (2020)
Concern about students dropping out of higher education institutions is a particularly stressful administrative issue for higher education institutions. Educational systems must assess efforts made by institutions to keep students enrolled until they progress academically and graduate understanding that educational quality is linked to managing retention. However, since 2000, there has been a greater focus on promoting actions for students to stay in school, by acknowledging that they play a key role in their own educational development and deciding to continue their studies, thus, highlighting the importance of strengthening links with the university and the educational system, as a whole. The concept of students dropping out of school is also reconsidered since studies have shown that many students do, in fact, return to school in the short and medium-terms. This study analyzes the administrative stress associated with students dropping out of school vs retention based on a literature review, specifically after the year 2000 that looks at the factors that impact a student´s decision to drop out of school and how this impacts traditional views permanently. As a result, a comprehensive and differentiated approach is required to address the dropout issue which involves organizational action, the need for students to establish and emotional connection with their studies, attain personal support and the student´s final decision by to drop out either temporarily or permanently.